E-Module Based Training Management with an Experiential Learning Approach to Enhance Project Based Learning (PjBL) Implementation by Teachers - Philip Putra Perdana; Wahyudi (Jurnal Ilmiah Pendidikan Profesi Guru, 2024)
This research is motivated by several problems that hinder the optimization of project-based learning. These include misconceptions about PjBL, inadequate teacher training that does not have a solid connection to experiential learning, which is the core principle of PjBL, and the need for experiential learning-based training e-modules for teachers. Therefore, this study aims to develop an e-module-based training management system using an experiential learning approach to improve teachers' ability to implement the PjBL model. This study utilized the Borg & Gall research and development methodology and the ADDIE model. The study used a mixed-methods approach, combining qualitative and quantitative methods. The subjects involved in this study were various subjects taught to teachers in senior high and junior high schools. Data collection methods included observation, interviews, and questionnaires. Qualitative data were analyzed using the Miles and Huberman method, while quantitative data were analyzed using descriptive statistics with scores and percentages. The research produced an e-module-based PjBL model training management product with an experiential learning approach that was presented as a website. This product obtained a validation score of 94% from IT experts and 88% from training management experts, and it received a limited trial score of 95%, which is an outstanding category. Based on these results, it is stated that the e-module product is valid and feasible to use in the learning process. Training on the PjBL model with an experiential learning approach can give teachers different experiences and a deeper understanding.